6-8x=3-9x

Simple and best practice solution for 6-8x=3-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-8x=3-9x equation:


Simplifying
6 + -8x = 3 + -9x

Solving
6 + -8x = 3 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
6 + -8x + 9x = 3 + -9x + 9x

Combine like terms: -8x + 9x = 1x
6 + 1x = 3 + -9x + 9x

Combine like terms: -9x + 9x = 0
6 + 1x = 3 + 0
6 + 1x = 3

Add '-6' to each side of the equation.
6 + -6 + 1x = 3 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 3 + -6
1x = 3 + -6

Combine like terms: 3 + -6 = -3
1x = -3

Divide each side by '1'.
x = -3

Simplifying
x = -3

See similar equations:

| 4x+18=14x-62 | | (3x+5)(8x-2)=(3x)(8x)+(3x)(-2)+(5)(8x)+(5)(-2) | | 9x+28=4x+103 | | 49-3x=8x+19 | | 2x+3y-5z=1 | | 6x-5=8+5x | | 5x+4=4x+4 | | X+7=34 | | 2x+10=4x-4 | | 408=10x+22 | | 3(y+6)-y=2(y-9) | | 2(5-x)=4x | | (2x+5)(4x-2)=(2x)(4x) | | (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 | | 5x^2-6x+4=0 | | 3a+8=20 | | 2a+9=17 | | a+1=4 | | X(3)=12 | | 16x-8y=64 | | 4(3q+7)=7 | | 7x+38=-4 |

Equations solver categories